(untitled) (Economic and Political Thought, 2016)
The Polish banking sector is dominated by foreign capital. The performance and development of banks are determined by the institutional and cultural circumstances of the host country, i.e. Poland. Most of the foreign bank owners come from countries where the market economy has long traditions and their societies are different in terms of perception and compliance with law. Thus, the article focuses on the importance of these differences for the development of the Polish banking sector. It also shows the main barriers and determinants related to the institutional and cultural context, including regulations and governance issues, which foreign capital must deal with. The presented opinions are based on the available literature, reports and own studies – 59 interviews conducted among the managerial staff of banks with foreign capital (current and former board members, supervisory boards and managing directors), as well as representatives of banking supervision (members of the Financial Supervision Commission).